Geographic and host distribution of haemosporidian parasite lineages from birds of the family Turdidae - Josef Harl; Tanja Himmel; Gediminas Valkiūnas; Mikas Ilgūnas; Támas Bakonyi; Herbert Weissenböck (Malaria Journal, 2020)
Abstract Background Haemosporidians (Apicomplexa, Protista) are obligate heteroxenous parasites of vertebrates and blood-sucking dipteran insects. Avian haemosporidians comprise more than 250 species traditionally classified into four genera, Plasmodium, Haemoproteus, Leucocytozoon, and Fallisia. However, analyses of the mitochondrial CytB gene revealed a vast variety of lineages not yet linked to morphospecies. This study aimed to analyse and discuss the data of haemosporidian lineages isolated from birds of the family Turdidae, to visualise host and geographic distribution using DNA haplotype networks and to suggest directions for taxonomy research on parasite species. Methods Haemosporidian CytB sequence data from 350 thrushes were analysed for the present study and complemented with CytB data of avian haemosporidians gathered from Genbank and MalAvi database. Maximum Likelihood trees were calculated to identify clades featuring lineages isolated from Turdidae species. For each clade, DNA haplotype networks were calculated and provided with information on host and geographic distribution. Results In species of the Turdidae, this study identified 82 Plasmodium, 37 Haemoproteus, and 119 Leucocytozoon lineages, 68, 28, and 112 of which are mainly found in this host group. Most of these lineages cluster in the clades, which are shown as DNA haplotype networks. The lineages of the Leucocytozoon clades were almost exclusively isolated from thrushes and usually were restricted to one host genus, whereas the Plasmodium and Haemoproteus networks featured multiple lineages also recovered from other passeriform and non-passeriform birds. Conclusion This study represents the first attempt to summarise information on the haemosporidian parasite lineages of a whole bird family. The analyses allowed the identification of numerous groups of related lineages, which have not been linked to morphologically defined species yet, and they revealed several cases in which CytB lineages were probably assigned to the wrong morphospecies. These taxonomic issues are addressed by comparing distributional patterns of the CytB lineages with data from the original species descriptions and further literature. The authors also discuss the availability of sequence data and emphasise that MalAvi database should be considered an extremely valuable addition to GenBank, but not a replacement.